Sustainable Stabilization of Expansive Soil Using Rice Husk Ash, Sisal Fiber, and Lime - Kamba, Assy; Nakamoga, Phiona; Kiwanuka, Moses; Niyomukiza, John Bosco (Universitas Diponegoro, 2025)
Expansive soils pose a major challenge to infrastructure stability due to their significant volumetric changes during wetting and drying cycles. Conventional stabilizers such as cement and lime are effective but carbon intensive. The use of agro-industrial residues combined with natural fibers presents a sustainable alternative, though it remains insufficiently investigated in tropical environments. This study examines the synergistic effects of rice husk ash (RHA), sisal fiber, and lime on the engineering behavior of expansive soil. Laboratory tests conducted in accordance with BS 1377 and ASTM standards included Atterberg limits, compaction, unconfined compressive strength (UCS), and California bearing ratio (CBR). XRF analysis confirmed the high silica content of RHA, indicating strong pozzolanic potential when blended with lime. The results showed that small percentages of RHA (12.5–17.5%) yielded the most significant improvements: plasticity index reduced from 32.6% to 12.7%, linear shrinkage decreased from 12.7% to 4.3%, the maximum UCS was 0.69 MPa, and soaked CBR increased to 48% compared with 3.8% in unstabilized soil. Beyond 17.5% RHA, strength and compaction performance declined due to excess fines and incomplete pozzolanic bonding. The findings from this study demonstrate that agro‑industrial residues and natural fibres can provide low‑carbon, locally sourced solutions for subgrade stabilization.